5‐5: Late‐News Paper: Low‐Power‐Consumption Flexible AMOLED Display with Highly Efficient TE‐Type Blue OLED. Issue 1 (29th May 2019) - Umeda, Tokiyoshi; Tsukamoto, Yuto; Zhang, Bai; Jo, Tomoaki; Imada, Hiroshi; Kawato, Shinichi; Mitsui, Seiichi
Abstract : Low‐power‐consumption 6.18" WQHD+ flexible AMOLED displays with highly efficient top‐emission type blue OLEDs have been developed. Using a blue emitter with narrow spectrum and short peak wavelength, which indicates deep blue chromaticity, the AMOLED displays show 11% lower power consumption at entire white image.